Prínos stanovení antigenu Helicobacter pylori ve stolici - Vlcková, P; Hep, A; Dolina, J; Stroblová, H; Dítĕ, P (Vnitrni lekarstvi, 2001)
Diagnostic methods for the detection of Helicobacter pylori (H.P.) can be divided into invasive and non-invasive ones. Among non-invasive methods we can include now also detection of H.P. antigen in faeces. The objective of our study was to evaluate the sensitivity ans specificity of the test when monitoring the eradication therapy, as compared with another non-invasive test and to test the method in common clincal practice. H.P. positivity was based on the result of the histological examination and CLO test. Repeatedly samples of faeces were collected to detect H.P. antigen in faeces before the onset of and after eradication treatment. For detection of H.P antigen the commercial Premier Platinum HpSa set was used which was developed on the principle of enzyme immunoanalysis. From the assembled data the sensitivity value (87.1%) and specificity values (88.5%) was calculated. The test correlates well with the results of the CLO test, histological examination and the breath test and is thus a suitable method for the detection of H.P. positive subjects as well as for checking the success of eradication treatment of H.P.
Keywords: Male; Feces; lidé středního věku; senzitivita a specificita; Antigens, Bacterial; Gastrointestinal Diseases; Humans; Middle Aged; mužské pohlaví; Female; gastrointestinální nemoci; Immunoenzyme Techniques; antigeny bakteriální; ženské pohlaví; feces; imunoenzymatické techniky; Sensitivity and Specificity; Helicobacter Infections; infekce vyvolané Helicobacter pylori; lidé; Helicobacter pylori